(untitled) (The Journal of Plant Protection Sciences, 2022)
Spread of yellow vein mosaic virus (YVMV) disease in different plant spacing 30 x 30 cm, 50 x 30 cm, 60 x 30 cm, 60 x 60 cm and 60 x 40 cm and using two cultivars, i.e., Cv. Parbhani Kranti and Local indicated that the first appearance of symptom was earlier in Cv. Local and late in Cv. Parbhani Kranti. The rate of infection was higher at 45 to 60 days after sowing in both kharif and summer while in Cv. Local it was higher at 30 to 45 days after sowing. Less infection rate was observed at 30 to 45 days after sowing in closer plant spacing 30 x 30 cm in both kharif and summer seasons also the minimum infection rate throughout its growth period was observed in closer plant spacing i.e. 30 x 30 cm in kharif. Among Cultivar Cv. Parbhani Kranti show slow progress of the disease. Among plant spacings the closer plant spacing 30 x 30 cm show slow progress of the disease followed by 50 x 30 cm and 60 x 30 cm both in kharif and summer seasons.